Energy dissipation of an infinite damping beam supported by saturated poroelastic halfspace. (8th March 2021) - Liu, Kuan; Hu, Weipeng; Gao, Chong; Ye, Wanjun
Abstract: Reproducing the dissipative effects in the non-conservative dynamic system numerically is one of the challenges in the numerical method because that, both the artificial dissipation of the numerical method and the real dissipation of the system are contained in the numerical results. In this paper, a complex structure-preserving numerical approach with tiny artificial dissipation is developed to investigate the energy dissipation in the road-foundation interaction system subjected to a moving load. Simplifying the road as an infinite damping beam with a finite width and the foundation as a saturated poroelastic halfspace with viscosity, the nonlinear coupling damping dynamic model is established. The energy dissipation laws of the road-foundation interaction system are revealed with different parameters of the moving load in the numerical simulations by the complex structure-preserving approach. The complex structure-preserving approach developed in this paper provides a new way to analyze the coupling dissipative problems. In addition, the energy dissipation laws obtained from the numerical results give some suggestions on the road design and the foundation design in engineering.